2019
DOI: 10.1176/appi.focus.17309
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Neurobiology of Bipolar Disorder

Abstract: Bipolar disorder (BD) is a leading cause of global disability. Its biological basis is unknown, and its treatment unsatisfactory. Here, we review two recent areas of progress. First, the discovery of risk genes and their implications, with a focus on voltage-gated calcium channels as part of the disease process and as a drug target. Second, facilitated by new technologies, it is increasingly apparent that the bipolar phenotype is more complex and nuanced than simply one of recurring manic and depressive episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 114 publications
(53 reference statements)
1
38
0
1
Order By: Relevance
“…The recent resurgence of interest in calcium in bipolar disorder has been fostered by the genomic data showing that VGCCs are part of the genetic risk architecture, implicating a role for Ca 2+ signalling in the disorder [12,16,17]. The question arises as to whether the genetic findings are directly related to the elevated intracellular [Ca 2+ ] observed in platelets and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent resurgence of interest in calcium in bipolar disorder has been fostered by the genomic data showing that VGCCs are part of the genetic risk architecture, implicating a role for Ca 2+ signalling in the disorder [12,16,17]. The question arises as to whether the genetic findings are directly related to the elevated intracellular [Ca 2+ ] observed in platelets and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade the study of Ca 2+ in bipolar disorder has been received new impetus from the increasingly compelling evidence that voltage-gated calcium channels (VGCCs) are part of the genetic aetiology [12,13]. Interest is enhanced by the therapeutic opportunities which VGCCs provide, given their known druggability by existing calcium channel blockers and the gabapentinoids [14][15][16][17]. However, despite multiple studies and several narrative reviews, there is no consensus as to the specific Ca 2+ abnormality-if any -which characterises bipolar disorder, nor is the robustness of the evidence clear [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated prevalence of AI in the general population is 14%, with levels being higher in younger people and women (Marwaha et al, 2013c;Patel et al, 2015). We (Broome et al, 2015a), and others (Harrison et al, 2017) have suggested that trans-diagnostic investigation of AI is compatible with the NIMH Research Domain Criteria project (Insel, 2014), a framework for understanding mental disorders by study of dysfunction in individual psychological and biological systems.…”
Section: Introductionmentioning
confidence: 89%
“…In the literature, dysfunction of voltage-gated ion channels has been implicated in the pathogenesis of bipolar disorder. Most notably, genome-wide analyses have implicated two genes, CACNA1C and ANK3, of which the former encodes a subunit of a voltagegated calcium channel and the latter encodes a protein coupling voltage-gated sodium channels to the axonal cytoskeleton [5].…”
Section: Discussionmentioning
confidence: 99%